Assessment of Soil Resilient Modulus Under Cyclic Loading Using Cyclic CBR Test Equipment - Ševelová, Lenka; Florian, Aleš; Žák, Jaroslav (Civil Engineering Journal, 2026)
Soil materials and road pavement construction materials are subjected to dynamic and repetitive loading of different intensity from vehicle traffic. To account for the cyclic nature of material loading and its non-linear behavior, the concept of the resilient modulus has been adopted. It is a fundamental property of unbound pavement materials, as it quantifies the stiffness of the material under repeated loading. Its real value depends on the actual material parameters—e.g., maximum dry density, moisture content, compaction method, and the number and magnitude of repeated loads—and on the state of stress of the actual pavement structure. The resilient modulus value is therefore not constant for a given material type but varies over a certain interval depending on the above-mentioned parameters and the actual test conditions. Therefore, the method of determining the resilient modulus must take into account all the above factors. The standard method for resilient modulus determination is the cyclic triaxial test, but the cyclic CBR test procedure is also used. It uses standard California Bearing Ratio (CBR) test equipment, and thus it is a very simple and very economical testing method. In the presented paper, the influence of loading force and number of loading cycles on the deformation characteristic and resilient modulus of the analyzed soil is investigated. A total of 72 soil specimens are tested at two different levels of loading force and six different numbers of loading cycles. The obtained results confirm that the resilience modulus increases with increasing loading force value and with increasing number of loading cycles. For the soil analyzed, the resilient modulus ranges in the interval 31-83 MPa.